CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE: EXAMINING THE MEDIATION OF MARKET PERFORMANCE AND THE MODERATING OF WOMEN ON BOARD - Hariyani, Eka; Zirman, Zirman; Basri, Yesi Mutia; Indriani, Sri (Universitas Riau, 2025)
This study examines the relationship between capital structure, market performance, and financial outcomes, while evaluating the moderating role of female board participation and the mediating role of market valuation. Using a quantitative approach with PLS-SEM on cross-sectional data from Kompas100-listed companies, the findings show that capital structure has no significant effect on financial performance or market valuation—contradicting traditional trade-off and signaling theories in an emerging market context. In contrast, market performance significantly influences financial outcomes, highlighting the importance of investor perception. Female board presence strengthens the impact of capital structure on market performance, supporting the upper echelon theory regarding leadership diversity. However, market performance does not mediate the link between capital structure and financial outcomes. These results suggest that financial decisions are shaped by external perceptions and firm context rather than following a linear pattern. Practically, firms are advised to adopt context-aware financing strategies, enhance transparency, and support inclusive governance for sustainable value creation.